Answer:
a) v(2) = 2m/s, v(3) = -2m/s
b) speed at t = 2s is 2m/s
speed at t = 3s is 2m/s
c) 0 m/s
Step-by-step explanation:
We can take the derivative of x(t) to find the equation of velocity
v(t) = x'(t) = 10 - 4t
(a) v(2) = 10 - 4*2 = 10 - 8 = 2 m/s
v(3) = 10 - 4*3 = 10 - 12 = -2 m/s
(b) The speed would be the same as velocity without the direction
speed at t = 2s is 2m/s
speed at t = 3s is 2m/s
(c) The average velocity between t = 2s and t = 3s is distance it travels over period of time
![v_a = (s(3) - s(2))/(\Delta t) = (10*3 - 2*3^2 - (10*2 - 2*2^2))/(3 - 2)](https://img.qammunity.org/2021/formulas/physics/high-school/iduv9nuvdpv3oylzlod6wzhwj1d4dp87iy.png)
![v_a = (12 - 12)/(1) = 0/1 = 0 m/s](https://img.qammunity.org/2021/formulas/physics/high-school/llnmpvzygthhihx48vd0g6l3mle8ntdqw4.png)